Innovation in Sharia Finance Products and Services - Kholijah, Siti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The facts show that the market share for Sharia financial industry products is still relatively small when compared to conventional financial products. The development of Sharia banking products and services that are competitive and based on the needs of the Indonesian people is a causality (cause and effect) that cannot be separated from reality. This research uses the Systematic Literature Review (SLR) method to collect, evaluate, and compile research results that are relevant to innovation in Sharia financial products and services. The results of this research show several developments, including increasing institutional capacity and the availability of Sharia financial industry products that are more competitive and efficient, with one program increasing the availability and diversity of Sharia financial products, both in Sharia banking institutions, Sharia capital markets, and the Sharia non-bank financial industry.